Exhuming and Preserving Epizonal Orogenic Au‐Sb Deposits in Rapidly Uplifting Orogenic Settings. Issue 8 (5th August 2022) - Yu, Hao‐Cheng; Qiu, Kun‐Feng; Deng, Jun; Zhu, Rui; Mathieu, Lucie; Sai, Sheng‐Xun; Sha, Wu‐Jin
Abstract: Epizonal orogenic Au‐Sb deposits are generally Phanerozoic in age, possibly as a consequence of erosion that can entirely remove older mineral deposits in rapidly uplifting orogenic setting. Quantifying post‐mineralization thermotectonic processes is essential for documenting the exhumation and preservation of epizonal deposits, which in turn is critical for constraining regional deformation. This study focuses on the giant Zaozigou deposit, and documents cooling rates using amphibole and biotite Ar‐Ar, zircon U‐Th/He, and apatite fission track dating. Six cooling phases are identified, including Early to Middle Triassic very rapid cooling, Late Triassic rapid cooling, Early Jurassic slow cooling, Middle to Late Jurassic rapid cooling, Cretaceous to Oligocene slow cooling, and Miocene to present rapid cooling. Initial cooling corresponds to thermal exchange between magmatic rocks and wall rocks. Phases two through five are related to a sequence of post‐mineralization compressional, strike‐slip, compressional, and extensional events, pointing to multi‐phase tectonic evolution of the Qinling Orogen since the Late Triassic. Late exhumation is probably related to lateral growth of the Tibetan Plateau and/or to rapid erosion induced by intensification of the Asian monsoon. In total, ∼6.3 km of rock was removed post‐mineralization. We conclude that Cretaceous to Oligocene extension retarded the continuous erosion and thus played an important role in the preservation of Zaozigou. Combined with known orogenic processes, our results demonstrate that a long‐lived extension is a favorable tectonic environment for the preservation of epizonal orogenic Au‐Sb deposits in rapidly uplifting orogenic setting. Plain Language Summary: Epizonal orogenic Au‐Sb deposits form at < ∼6 km depth in orogenic setting and supply large amounts of Au and most of the Sb to the world economy. They are generally Phanerozoic in age, possibly as a consequence of erosion that can entirely remove older mineral deposits in rapidly uplifting. Regional deformation related to tectonic evolution of orogen is therefore critical for exhumation and preservation of epizonal deposits. This study documents exhumation rates on the giant Zaozigou deposit in the Qinling Orogen in central China. Multi‐cooling phases are related to a sequence of compressional, strike‐slip, compressional, and extensional processes occurring after mineralization. Our results demonstrate that a long‐lived extension signifies a favorable tectonic environment for the preservation of epizonal orogenic Au‐Sb deposits in rapidly uplifting orogenic setting. Key Points: Thermochronological data constrain thermal history of epizonal Au‐Sb deposits Most epizonal deposits were eroded in rapidly uplifting orogenic settings A long‐lived extension is favorable for preservation of epizonal deposits